Scientific assimilation in the interpretation of the qur’ān: an approach to zaghlūl el-najjār’s work entitled “tafsīr Al-Ayah Al-Kawnīyyah Fī Al-Qur’ān Al-Karīm” - Amir, S.; Mohd Noor, M.M.; Ahmad Hilmi, A.B. (Brill Academic Publishers, 2012)

(untitled)
The advancement of science and technology which has been in par with the urbanization of knowledge requires careful analytic by the Muslims in order to have a better understanding of maqasid al-Quran in its multi dimension in accordance to syar’I factions. Thus, the manhaj that has been introduced by Prof Dr. Zaghlul al-Najjar through his scientific interpretation technique which can be found in his work; Tafsir Al-Ayah Al-Kawniyyah Fi Al-Quran Al-Karim has brought about such a sound impact in the understanding of bait tauhidik (tauhidic verses) in line with the current context. Through the method of analyzing the scientific data, he tried studying the Quranic verse, in particular the al-kawniyyah verses that comprises the aspects of creation of the universe (astronomy, astrology, geology dan natural phenomenon), human health and creation (embryology, archeology, physiology). Although it is the scientific arguments that dominate his works, the application of classical method in explaining the quranic verses were also featured in his work, especially in understanding the Quran textually that has been done through lughowi dimension. Hence, in this article, it aims to bring to light Prof. Dr. Zaghlul al-Najjar’s method in interacting with the Quranic verses through the discovery of data and scientific empirical in his work Tafsir Al-Ayah Al-Kawniyyah Fi Al-Quran Al-Karim.